IoT-School Attendance System Using RFID Technology - El Mrabet, Hicham; Ait Moussa, Abdelaziz (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Nowadays, the world has known great changes which accelerated the mode of life. Students, on their part have become to expect a stimulating and simple learning experience which takes into consideration this quick pace and helps them solve the stereotypical problems of learning. The analyses conducted in this paper revealed that the recording of attendance in classrooms is done at the expense of the teaching- learning time. Therefore, the article at hand seeks to investigate an effective means to record attendance in a way which doesn’t hinder learning. Differently put, the educational and administrative staffs need to find an effective way to record students’ attendance at presential at the beginning of each learning session without affecting the time allotted to teaching and learning. This article presents and discusses the smart attendance monitoring system in smart classroom as a means to reduce the dropout rate, using connected objects and RFID technology. This system can facilitate the recording of students’ attendance via the Internet of things (IoT) at presential while transmitting attendance record to the administration. At the same time, parents can keep track of their children's attendance to classes through a notification they receive via Email or SMS. In addition, the system automatically sends missed lessons to absent students.